Леся Українка – літературний критик: особливості „жіночого письма” - Корбич, Г. (Інститут літератури ім. Т.Г. Шевченка НАН України, 2007)
Розглядається літературно-критична практика Лесі Українки як культурна модель гінокритики. Доводиться, що на тлі української критики ХІХ – поч. ХХ ст. з її чоловічою доменою постать поетеси є „інакшою”, вона вносить дух відмінності, уособлюючи жіночий наратив з його пошуками комунікативного середовища. The paper analyses the characteristic features of Lesya Ukrainka’s literary and critical practice in the context of feminist criticism. The author of the paper aims at a conclusion stating that Lesya Ukrainka as a critic holds a different or even independent position in Ukrainian literary criticism, which at the turn of the 19th and the 20th century was an exclusively male privilege. The poet evidently introduces ‘a spirit of otherness’, creating a feminine style and communication strategies. Her communication model is based mainly on seeking a consensus between the critic and the reader, and on speaking the language of community and intimacy (which is characteristic of women in contrast to the masculine language of independence and status).